Evaluating HPV Vaccination‐Related Content on a Burgeoning Social Media Platform: Insufficient Quality of TikTok - Matthew E. Lin; Oluwatobiloba Ayo‐Ajibola; Carlos X. Castellanos; Jonathan D. West; Neil Luu; Niels C. Kokot (OTO Open)
Abstract Objective Assessing the quality of human papillomavirus (HPV) vaccination‐related content on TikTok is crucial due to its popularity among adolescents. We assessed these videos while comparing the content and quality of videos with and without physician involvement. Study Design Cross‐sectional cohort analysis. Setting HPV vaccination‐related TikTok videos. Methods The TikTok library was queried using the search terms #HPVvaccine, #HPVvaccination, #Gardasil, #Gardasilvaccine, and #Gardasilvaccination. Video quality was evaluated using the DISCERN scale, assessing treatment‐related information quality. Descriptive statistics were used to characterize our cohort. t Test and Fischer's exact test were used to assess for differences in video content and quality based on physician involvement. Significance was set at P < .05. Results Our search yielded 131 videos, averaging 68,503.12 views, 2314.27 likes, and 89.28 comments per video. Videos frequently involved physicians (48.09%), focused on education (54.96%) or advocacy (22.90%), and were US‐made (68.90%). Otolaryngologists were rarely featured (3.17%). While most videos mentioned the HPV vaccine protected against cancer generally (86.26%), and cervical cancer specifically (67.94%), few discussed its protective effect against head and neck cancer (26.72%). Videos infrequently discussed updated eligibility among all adults ≤45 years of age (26.72%) or that men can also receive the vaccine (28.24%). Physician‐involved videos were more focused on education (P < .001) and focused less on patient experiences (P < .001) and advocacy (P = .036). Overall DISCERN scores were low among physician (mean = 2.46, SD = 1.13) and nonphysician (mean = 2.09, SD = 1.02) content. Conclusion TikTok HPV vaccination content is poor in quality, even with physician involvement. Enhancing content quality and increasing otolaryngologist participation can boost HPV awareness and vaccination rates.